Nautical Graffiti from the Torre de Rame (Los Alcázares): Probable Evidence of Ottoman-Berber Harassment Along the Coasts of the Former Kingdom of Murcia (Spain) - Castejón Porcel, Gregorio (The international journal of nautical archaeology, 2024)
The discovery of historical graffiti in the Torre de Rame, a 17th-century watchtower built in Los Alcázares (Region of Murcia, Spain), has led to the study of a valuable and large set of nautical graffiti. The analysis of these representations, together with that of the tower, reveals that they represent vessels that crossed the Mediterranean Sea at a time when there was confrontation between Ottoman-Berber pirates and Corsairs and the Christian kingdoms. This, together with other evidence, suggests that the authors of these motifs engraved on the walls were sailors who were part of this tragic struggle.